Population biology and distribution of the portunid crab Callinectes ornatus (Decapoda: Brachyura) in an estuary-bay complex of southern Brazil - Watanabe, Timoteo T.; Sant'anna, Bruno S.; Hattori, Gustavo Y.; Zara, Fernando J. [UNESP] (Sociedade Brasileira de Zoologia, 2014)
Trawl fisheries are associated with catches of swimming crabs, which are an important economic resource for commercial as well for small-scale fisheries. This study evaluated the population biology and distribution of the swimming crab Callinectes ornatus (Ordway, 1863) in the Estuary-Bay of São Vicente, state of São Paulo, Brazil. Crabs were collected from a shrimp fishing boat equipped with a semi-balloon otter-trawl net, on eight transects (four in the estuary and four in the bay) from March 2007 through February 2008. Specimens caught were identified, sexed and measured. Samples of bottom water were collected and the temperature and salinity measured. A total of 618 crabs were captured (332 males, 267 females and 19 ovigerous females), with a sex ratio close to 1:1. A large number of juveniles were captured (77.67%). Crab spatial distributions were positively correlated with salinity (Rs = 0.73, p = 0.0395) and temperature (Rs = 0.71, p = 0.0092). Two peaks of recruitment occurred, in summer and autumn, and ovigerous females were mostly captured during summer, showing a seasonal reproductive pattern. The results showed that C. ornatus uses the bay as a nursery area for juvenile development. Callinectes ornatus is not yet a legally protected species, and the minimum allowed size of crabs caught in the area, although already restricted, should be carefully evaluated since the removal of large numbers of juveniles could negatively impact the local population.
Keywords: Migration; population biology; seasonal distribution; swimming crab